Protein Synthesis During Fungal Spore Germination: Differential Protein Synthesis During Germination of Botryodiplodia theobromae Spores - Van Etten, James L. (1972)
The preformed messenger ribonucleic acid in Botryodiplodia theobromae spores directs the synthesis of several relatively stable polypeptides